2016
DOI: 10.17265/2159-5542/2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Emotional Intelligence and Academic Achievements in Males and Females in Egyptian Context

Abstract: The present study examines the relationship among emotional intelligence, achievement, and gender. The sample consists of 121 participants at a public university in North Upper Egypt called Minia University. The Wong & Law's (2002) emotional intelligence scale has been used in this study. Confirmatory factor analysis has been adopted to verify the structure validity of the EI scale. Results of confirmatory factor analysis showed that the four-factor model fits well and its results meet the criteria for goodnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…It helps one build a stronger relationships to succeed at schools, achieve one's career and personal goals as well as enhance academic achievement in mathematics. Ali and Ali (2016) in their study found that emotional intelligence is positively correlated to students' academic achievement. Alghamdi, (2014) believes that higher levels of emotional intelligence predict academic achievement.…”
Section: Introductionmentioning
confidence: 93%
“…It helps one build a stronger relationships to succeed at schools, achieve one's career and personal goals as well as enhance academic achievement in mathematics. Ali and Ali (2016) in their study found that emotional intelligence is positively correlated to students' academic achievement. Alghamdi, (2014) believes that higher levels of emotional intelligence predict academic achievement.…”
Section: Introductionmentioning
confidence: 93%
“…The significant link discovered between EI and student academic achievement could pique curriculum developers' interest in learning more about EI's impact on achievement. Many studies have shown that emotional intelligence has a positive impact on academic performance (Mustafa Ali Khalaf, 2016;Preeti, 2013;Rode et al, 2007). In other studies, the connection between emotional intelligence and achievement was weak but important (Festus, 2012).…”
Section: Positive Relationships Between the Emotional Intelligence Factors And Academicmentioning
confidence: 99%
“…This questionnaire is widely used in Arabian contexts and thus enables culturally sensitive measurement (Ali & Ali, 2016;Sabbah et al, 2020). In this study, the Cronbach alpha was calculated and determined to be 0.91.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Previous research has found support for the underlying four‐factor structure, reliability and convergent and discriminant validity of the WLEIS scores (Law et al., 2004, 2008; Shi & Wang, 2007; Wong & Law, 2002a, 2002b). This questionnaire is widely used in Arabian contexts and thus enables culturally sensitive measurement (Ali & Ali, 2016; Sabbah et al., 2020). In this study, the Cronbach alpha was calculated and determined to be 0.91.…”
Section: Instrumentsmentioning
confidence: 99%